2020
DOI: 10.1126/sciadv.aaz6105
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of tumor-associated macrophages by targeting β-catenin/FOSL2/ARID5A signaling: A potential treatment of lung cancer

Abstract: Tumor-associated macrophages (TAMs) influence lung tumor development by inducing immunosuppression. Transcriptome analysis of TAMs isolated from human lung tumor tissues revealed an up-regulation of the Wnt/β-catenin pathway. These findings were reproduced in a newly developed in vitro “trained” TAM model. Pharmacological and macrophage-specific genetic ablation of β-catenin reprogrammed M2-like TAMs to M1-like TAMs both in vitro and in various in vivo models, which was linked with the suppression of primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 49 publications
4
107
0
Order By: Relevance
“…Accumulating evidence has suggested that TAMs originate from blood monocytes, and are recruited at tumor sites by tumor-derived chemotactic signals, including monocyte chemo-attractant protein-1 (MCP-1), which is also known as CCL2 ( 11 13 ). Furthermore, a small wave develops from in situ monocyte-macrophage proliferation and splenic monocytes.…”
Section: Macrophage Plasticity In Lung Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested that TAMs originate from blood monocytes, and are recruited at tumor sites by tumor-derived chemotactic signals, including monocyte chemo-attractant protein-1 (MCP-1), which is also known as CCL2 ( 11 13 ). Furthermore, a small wave develops from in situ monocyte-macrophage proliferation and splenic monocytes.…”
Section: Macrophage Plasticity In Lung Cancer Developmentmentioning
confidence: 99%
“…Clinical studies have suggested that increased TAM density correlates with a poor prognosis in solid tumors ( 5 , 7 , 8 ) Several animal model experiments have validated this observation by demonstrating that increased TAM density is associated with tumor progression and metastasis, and overexpression of macrophage growth factors or chemokines ( 9 , 10 ). The deletion or re-differentiation of TAMs enhances immune cell-mediated anti-tumor responses and benefits from chemotherapy ( 11 13 ). Therefore, targeting TAMs may be at the forefront of lung cancer research and a novel strategy for lung cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of tumor-derived type-2 cytokines, colony-stimulating factor 1 (CSF-1 or M-CSF), CCL2, and CCL4, adjacent lymphocytes become Th2-shifted, while tissue-resident macrophages and blood monocytes are attracted and converted to the M2 phenotype [40-44], as demonstrated by analysis of human lung cancer specimens and in vitro studies. The phenotypic switch of macrophages appears to rely on epigenetic changes [45] and Wnt signaling [46] and is of key importance, because tumor-associated M2 macrophages (TAMs) orchestrate several vicious cycles in the TME [47, 48] to promote: (i) tumor-cell growth by secretion of epidermal growth factor (EGF), matrix metallopeptidases, Wnt family member (WNT) 5A, cathepsin B, semaphorin 4D, and IL-1β [49]; (ii) DNA damage by suppressing p53 through macrophage migration inhibitory factor [50]; (iii) angiogenesis, tumor-endothelial cell dysfunction, and lymphangiogenesis by secretion of VEGF, IL-8, and matrix metallopeptidase-9 [51-53]; (iv) invasion, epithelial-to-mesenchymal transition, and metastasis [54-57]. Besides, TAM-derived TGFβ and chemokines synergize with contact signals from tumor cells to convert tissue-resident fibroblasts, mast cells, and blood-derived neutrophils to smooth-muscle actin-α-expressing cancer-associated fibroblasts (CAFs), tumor-associated mast cells (TAMCs), and tumor-associated neutrophils (TANs), respectively, whose secretome amplifies all tumorigenic effects [58-60].…”
Section: Immunopathogenesis Of Lung Cancermentioning
confidence: 99%
“…For RNA-seq, as previously described [28], we isolated RNA from A549-FGF14 overexpressing cells and empty vector control cells. The statistical significance of differentially expressed genes (DEGs) were analyzed based on a combination of absolute expression (basemean), divergence (log2 fold change, log2fc), and significance (adjusted p-value, padj).…”
Section: Transcriptome Analysesmentioning
confidence: 99%